Framework CSS: Tailwind CSS Untuk Front-End Website Store PT. XYZ - Azhariyah, Sari; Muhammad Mukhlis (LPPM Universitas Nias Raya, 2024)
This research aims to apply Tailwind CSS as a CSS Framework on the website store’s PT. XYZ to be more responsive and have the freedom to determine the style and layout according to the analysis of website needs. This study was carried out at PT. XYZ in Subang Regency, where conducting product transactions with customers needs the creation of a store website. The phases of requirements analysis, design, implementation, and modification are all included in the research methodology. The UI/UX design at PT is reflected in the front end of the website store. Utilize utility classes to create UI elements in Tailwind CSS during the front-end design phase. It has been demonstrated that you may implement internet shop display designs more rapidly and freely give styles and layouts according to your demands by using the Tailwind CSS Framework. In addition, the responsive display facilitates cross-platform user experience by making it simpler for customers to complete transactions.